2010
DOI: 10.1002/ar.21081
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Heart Rate Reduction Facilitates Cardiomyocyte Survival After Myocardial Infarction

Abstract: Chronic heart rate reduction (HRR) therapy following myocardial infarction, using either the pure HRR agent ivabradine or the b-blocker atenolol, has been shown to preserve maximal coronary perfusion, via reduction of perivascular collagen and a decrease in renin-angiotensin system activation. In addition ivabradine, but not atenolol, treatment attenuated the decline in ejection fraction and decreased left ventricular wall stress. In this study, we tested the hypothesis that cell survival within the infarct re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
15
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 40 publications
7
15
0
1
Order By: Relevance
“…In the granulation phase of infarct healing, our results are in agreement with previous work showing that heart rate reduction could enhance postinfarction angiogenesis by upregulating proangiogenic factors (28,30,56). Moreover, pharmacologically induced chronic heart rate reduction could give rise to a dramatic improvement of infarct size and myocardial survival in rats (55). Taken together, from the very beginning until the chronic phase after MI, LV mechanical unloading and heart rate reduction could be the key mechanisms underlying the massive myocardial salvage observed in this work.…”
Section: Discussionsupporting
confidence: 92%
“…In the granulation phase of infarct healing, our results are in agreement with previous work showing that heart rate reduction could enhance postinfarction angiogenesis by upregulating proangiogenic factors (28,30,56). Moreover, pharmacologically induced chronic heart rate reduction could give rise to a dramatic improvement of infarct size and myocardial survival in rats (55). Taken together, from the very beginning until the chronic phase after MI, LV mechanical unloading and heart rate reduction could be the key mechanisms underlying the massive myocardial salvage observed in this work.…”
Section: Discussionsupporting
confidence: 92%
“…They also concluded that these beneficial effects resulted in the prevention of endothelial dysfunction. Recently, Zhang et al [37] declared that heart rate reduction therapy using ivabradine following myocardial infarction has been shown to preserve maximal coronary perfusion via the reduction of perivascular collagen and to decrease renin-angiotensin system activation. The researchers concluded that heart rate reduction by ivabradine facilitates a more favorable O 2 microenvironment via improved venous flow and decreased O 2 demand.…”
Section: Discussionmentioning
confidence: 99%
“…However, young or even adult rodents are not suitable as models of myocardial infarction in humans, because myocardial infarctions occur primarily in middle-aged and older individuals (Bairey Merz et al 2006). The importance of using older animals in MI experiments, especially in the case of small rodents, has been compelled by the findings of studies published earlier by our group (Christensen et al 2009;Dedkov et al 2005;Dedkov, Zheng, et al 2007;Zhang et al 2010) and other laboratories (Kranz et al 1975;Wexler 1978;Raya et al 1997;Bujak et al 2008;Yang et al 2008), which In all scars, densely packed collagen fibers were noticed along the endocardial and epicardial surfaces, including subendocardial and subepicardial regions with surviving cardiac myocytes (CM) (arrows), in areas around the residual coronary arteries (A), and in the midwall layer where they occasionally embedded the remnants of mummified dead CM (arrowheads). On the other hand, loosely packed collagen fibers were dispersed through the rest of the scar.…”
Section: Sex-related Differences In LV Remodeling and Scar Formationmentioning
confidence: 99%
“…Some of these scar components have been shown to undergo a dynamic reorganization in response to ongoing LV remodeling (Whittaker 1995;Sun and Weber 2000;Sun et al 2002;van den Borne et al 2010). Surprisingly, in the previous in vivo studies that used either male or female animals, only a few used quantitative methods to examine the structural composition of the post-MI scars (Boyle and Weisman 1993;Hayakawa et al 2003;Virag and Murry 2003;Lichtenauer et al 2011;Zhang et al 2010).…”
mentioning
confidence: 99%